2020
DOI: 10.3390/app10113800
|View full text |Cite
|
Sign up to set email alerts
|

Phenological Model Intercomparison for Estimating Grapevine Budbreak Date (Vitis vinifera L.) in Europe

Abstract: Budbreak date in grapevine is strictly dependent on temperature, and the correct simulation of its occurrence is of great interest since it may have major consequences on the final yield and quality. In this study, we evaluated the reliability for budbreak simulation of two modeling approaches, the chilling-forcing (CF), which describes the entire dormancy period (endo- and eco-dormancy) and the forcing approach (F), which only describes the eco-dormancy. For this, we selected six phenological models that appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 53 publications
1
40
0
1
Order By: Relevance
“…While many studies have investigated the effect of temperature, and thus climate change, on grapevine phenology, these studies generally relate to individual grape-growing regions. Although some comparisons have been made (for example using modelling simulations (Leolini et al, 2020), comparisons between regions or vineyards using observed changes in phenology are rarely made. This study aimed to analyse previously published data from different vineyards and different climates to compare trends for the major phenological stages between these vineyards, to determine whether there were differences in the rate of change of advancement of these phenological stages between the different vineyards.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have investigated the effect of temperature, and thus climate change, on grapevine phenology, these studies generally relate to individual grape-growing regions. Although some comparisons have been made (for example using modelling simulations (Leolini et al, 2020), comparisons between regions or vineyards using observed changes in phenology are rarely made. This study aimed to analyse previously published data from different vineyards and different climates to compare trends for the major phenological stages between these vineyards, to determine whether there were differences in the rate of change of advancement of these phenological stages between the different vineyards.…”
Section: Introductionmentioning
confidence: 99%
“…Budburst is one of the most important stages of development, as it represents the start of vegetative growth. An increase in temperature can bring advances or delays in its start date, inducing important consequences in the following reproductive stages [ 63 ]. During winter, the grapevine enters into a dormant state to overcome adverse conditions by means of interruption of the growth [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The starting date of January 1st of the current year showed a small improvement in efficiency, according to some authors that suggest a start date of the thermal accumulation during the first days of the year [ 46 , 68 ]. Leolini and collaborators [ 63 ] revealed that January 1st seems to be more suitable for assessing the budburst date of the vine varieties collected in Southern Europe. Our study showed the initial date for the thermal sum of the budburst stage occurred in late winter (February and March).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ripening period is indeed not only shifting toward the warmest period of summer, at least in the Northern hemisphere, but also temperatures are higher on the same calendar day ( Molitor and Junk, 2019 ). The extent of the advances of budburst dates is still uncertain because they depend on the dates of dormancy release ( Leolini et al, 2020 ), which are difficult to observe and therefore to model. Higher risks of spring frost after budburst should not be overlooked and could increase in vineyards in northern France ( Sgubin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%